Increasing Awareness Cadres Regrading Environmental Cleanliness in Handling Dangue Fever Mosquito Flars - Akas Yekti Pulih Asih; Budhi Setianto; Agus Aan Adriansyah; Abdul Hakim Zakkiy Fasya; Yauwan Tobing Lukiyono; Mery Susantri; Nikmatus Sa'adah (UNUSA Press, 2025)
Background: Several incidents of dengue fever cases in residents of RW 07 Pulowonokromo indicate that the large number of mosquitoes that cause dengue fever are attacking residents, dense environments and riverbank areas, which causes mosquitoes to breed quickly and it is necessary to prevent mosquito larvae. The dengue mosquito cycle begins with the Ae mosquito cycle. aegypti L. reproduce and undergo complete metamorphosis. Objective: This community service aims to make residents aware of the importance of breaking the chain of the Aedes agepti mosquito, thereby minimizing the incidence of dengue fever in residents. Method: The method used is to hold a workshop which is attended by cadre mothers Results: the workshop attended by residents had a positive impact. Conclusion: From the activities that were attended by cadres of RW 07 Residents, Wonokromo Subdistrict, Wonokromo District, Surabaya City, which were attended by 52 participants with the characteristics of providing information that most of the workshop participants were high school educated and aged < 50 years with the profession of housewives who were very enthusiastic and full of enthusiasm in its implementation, this training was very beneficial to the participants and there was an increase in knowledge from the results of the pretest and posttest from the results of the correlation paired t-test. There was a significant difference between the Pre-Test and Post-Test based on the results of the Paired Sample T-Test with an Alpha of 5%.